Impact of Extratumoral Lymphatic Permeation on Postoperative Survival of Non–Small-Cell Lung Cancer Patients - Matsumura, Yuki (Lippincott Williams & Wilkins, 2014)
INTRODUCTION: Lymphatic permeation has been reported as a prognostic factor for patients with resected non–small-cell lung cancer (NSCLC). Lymphatic canals are located in both intratumoral and extratumoral areas. Since 2001, we have prospectively evaluated lymphatic permeation based on its location. The purpose of this study was to determine the survival impact of extratumoral lymphatic permeation in patients with resected NSCLC by analyzing the long-term follow-up data. METHODS: We reviewed 1069 consecutive patients with NSCLC who underwent complete resection between 2001 and 2006. Lymphatic permeation was classified as follows: ly0, absence of lymphatic permeation; ly1, intratumoral; and ly2, extratumoral. RESULTS: There were 845 patients (79%) with ly0, 134 (12%) with ly1, and 90 (9%) with ly2. Ly2 was more frequently observed in patients with advanced disease and intrapulmonary metastases than ly0–1. The 5-year overall survival (OS) rates of the ly0, ly1, and ly2 groups were 75%, 63%, and 34%, respectively. The OS rate was significantly worse in the ly2 group compared with OS rate in the ly0 (p < 0.01) and ly1 groups (p < 0.01). In multivariate analyses, ly2 proved to be an independent poor prognostic factor (hazard ratio, 1.73; p < 0.01). OS and recurrence-free survival of patients with T1 and T2 tumors with ly2 were not statistically different from that of the patients with T3 tumor (OS, p = 0.43 and p = 0.77; recurrence-free survival, p = 0.94 and p = 0.94, respectively). CONCLUSIONS: The adverse prognostic impact of lymphatic permeation was remarkably different whether it is detected in intratumoral or extratumoral lymphatic canals. We recommend that lymphatic permeation in resected NSCLC should be evaluated by considering its location.